Small Polaron Hopping to Efros–Shklovskii-Like Variable Range Hopping Transition in Graphene-Wrapped V2O5 Nanoparticles: The Roleplay of the Mott Gap - Bhaskaram, D. Surya; Govindaraj, G. (Journal of physical chemistry. C, 2023)
V2O5 is a promising candidate in varied fields and has proven to favor polaron formation. Polarons are slow-moving with extra mass, thus affecting conductivity. Charge transport/conductivity is one of the key factors deciding device utility and is compromised due to the slow motion of polarons. To solve this, incorporating graphene into V2O5 is widely practiced. V2O5 exhibiting small polaron hopping is a fact, and variable range hopping of highly mobile electrons is observed in graphene at low temperatures. The inclusion of graphene into V2O5 shows conductivity enhancement and hence has been widely studied for varied applications. The reason for conductivity enhancement is considered to be the presence of delocalized electrons in graphene, which makes the sample electron-rich and increases conductivity. But the actual mechanism of conductivity enhancement is unclear. This led us to explore the electrical properties of graphene-wrapped V2O5. To our surprise, the inclusion of graphene completely changes the dynamics of charge carriers. Polarons in composite chose variable range hopping over Arrhenius-type small polaron hopping in the temperature range of 143–263 K. ac conductivity σ′(ω) data of V2O5 and reduced graphene oxide (RGO)-wrapped V2O5 are analyzed using the Cole–Cole-type combined conduction and dielectric model. σdc of polarons shows T –1 dependence for V2O5 and T –1/2 dependence for RGO-wrapped V2O5 (VRGO). In general, at low temperatures (T < 100 K), such behavior is interpreted to be Efros–Shklovskii (ES) VRH, but the temperature range (143–263 K) that we have covered cannot justify ES-VRH. A detailed overview of the carrier environment is carried out using tools such as XRD and temperature-dependent Raman along with conductivity measurements to account for the T –1/2 dependence of polarons. The results of various measurements point toward the origin of Mott gap in V2O5 after incorporating graphene into it, thus controlling the surprising behavior of polarons.